Arbitration or Litigation: International High-Tech Business Disputes Resolutions - Elfakharani, Ashraf M. A.; Rahman, Rohana Abdul; Abdullah, Nor Anita (American Journal of Social Sciences and Humanities, 2019)
This paper discusses a dichotomy that arises on the issue of choosing the right dispute settlement mechanism in matters related to high-tech companies. Such disputes arise in complex issues related to Patents and IPR rights, product piracy, counterfeiting, internet and cyber security and several issues related to marketing and territorial rights of selling scientific products. These cases cannot be handled in traditional court for several reasons. Instead businesses are turning to alternative dispute resolution (ADR) for instance arbitrations institutions like SVAMC that works with high-tech companies and law firms and advocate the promotion of arbitration mechanism to resolve high-tech business disputes. Other international institute such as World Intellectual Property Organization (WIPO) ADR in R&D and technology that has many advantages over normal litigation including low costs, very short time taken to settle disputes and predictability. This paper compares the different approaches in the traditional courts litigation system and ADR in respect of high-tech business disputes and recommends why arbitration is a more preferred method to solve high-tech disputes.